PENGGUNAAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PUISI - Sukaharsilawati, Made Ayu (Widyadari: Jurnal Pendidikan, 2018)
This research has an objective to improve the teaching of Indonesian language and literature, and to improve students' poetry reading skill of class XII AP 2 SMK Nusa Dua Badung in lesson 2014/2015 through contextual approach (CTL). The results of this study is the ability of students of class XII AP 2 SMK Nusa Dua Badung in reading poetry is very good. It is evident from the average value obtained by students have increased from each cycle. In cycle I the average of students is 70.71%. In cycle II the average score of students' poetry reading ability increased to 82.28%.